Diversity of polyester-degrading bacteria in compost and molecular analysis of a thermoactive esterase from Thermobifida alba AHK119 - Hu, Xiaoping; Thumarat, Uschara; Zhang, Xian; Tang, Ming; Kawai, Fusako (Applied microbiology and biotechnology, 2010)
More than 100 bacterial strains were isolated from composted polyester films and categorized into two groups, Actinomycetes (four genera) and Bacillus (three genera). Of these isolates, Thermobifida alba strain AHK119 (AB298783) was shown to possess the ability to significantly degrade aliphatic-aromatic copolyester film as well as decreasing the polymer particle sizes when grown at 50°C on LB medium supplemented with polymer particles, yielding terephthalic acid. The esterase gene ( est119 , 903 bp, encoding a signal peptide and a mature protein of 34 and 266 amino acids, respectively) was cloned from AHK119. The Est119 sequence contains a conserved lipase box (–G-X-S-X-G-) and a catalytic triad (Ser129, His207, and Asp175). Furthermore, Tyr59 and Met130 likely form an oxyanion hole. The recombinant enzyme was purified from cell-free extracts of Escherichia coli Rosetta-gami B (DE3) harboring pQE80L- est119 . The enzyme is a monomeric protein of ca. 30 kDa, which is active from 20°C to 75°C (with an optimal range of 45 to 55°C) and in a pH range of 5.5 to 7.0 (with an optimal pH of 6.0). Its preferred substrate among the p -nitrophenyl acyl esters (C 2 to C 8 ) is p -nitrophenyl hexanoate (C 6 ), indicating that the enzyme is an esterase rather than a lipase.